Real-world adverse event profile and signal characteristics of bevacizumab in glioma: a FAERS-based disproportionality analysis - Gao, Mingyue; Chen, Qiao; Zhang, Hengheng; Tian, Yi; Fu, Zhiguang; Yan, Maohui; Liu, Chen (Frontiers in Pharmacology, 2026)
BackgroundBevacizumab is a critical anti-angiogenic therapy for glioma, but its real-world safety profile requires comprehensive characterization beyond clinical trials to effectively manage treatment risks.MethodsThis pharmacovigilance study analyzed adverse event reports from the FDA Adverse Event Reporting System (FAERS) for glioma patients receiving bevacizumab. A disproportionate analysis using multiple analytical methods was conducted to identify significant safety signals. Subgroup analyses stratified by gender and age were performed to explore population heterogeneity.ResultsBevacizumab-related AEs involved multiple system organ classes, with particularly prominent disproportionality signals for vascular disorders, especially hypertension, proteinuria and thromboembolic events such as pulmonary embolism. Most AEs occurred within the early treatment period, but late-onset events, including tumor progression, still accounted for a notable proportion. Subgroup analysis indicated that male patients were at higher risk of overall bleeding and thrombotic events, whereas female patients more frequently reported cognitive impairment and showed stronger signals for severe bleeding subtypes such as intracranial hemorrhage, suggesting sex-specific heterogeneity across bleeding phenotypes. Middle-aged patients bore the greatest burden of reported AEs.ConclusionThis study delineates the adverse event spectrum of bevacizumab in patients with glioma, confirming prominent vascular and renal toxicities and revealing sex- and age-related differences in safety profiles. The findings highlight the need for heightened surveillance of vascular and renal events following bevacizumab exposure and provide hypothesis-generating evidence to inform future prospective studies.